Psychological Impact of Implementing a Parenting Program Based on Systemic Functional Linguistics and Appraisal for Parents in Garut - Nurjamin, Lucky Rahayu; Nurjamin, Asep; Soni, Mohamad; Fajriah, Yustika Nur; Norani, Norani; Ridhwan, Rafli Muhamad; Maulana, Ridwan; Dwiputri, Cahyani (Indonesian Journal of Community Empowerment (IJCE), 2025)
The Orang Tua Tangguh Program was implemented to strengthen parental emotional resilience and positive parenting practices among members of the Kelompok Keluarga Sehat Berdaya (KKSB) in Garut Regency. Grounded in the Lazarus–Folkman Appraisal Theory and Systemic Functional Linguistic (SFL) Appraisal, the program combined psychoeducation, language-based parenting training, reflective journaling, and group counseling over a two-month period. A total of 25 parents, primarily mothers of children aged 4–6 years, participated actively with an average attendance rate of 82%. The program led to notable improvements in parental emotional regulation, confidence, and communication patterns, with participants reporting reduced emotional outbursts and increased use of empathetic, validating language toward children. These behavioral changes contributed to better child responsiveness, decreased daily conflicts, and emerging emotional expression skills among young children. At the community level, the initiative produced a practical module on positive parenting language and fostered local role models who now support neighboring families. The findings demonstrate that integrating linguistic appraisal with psychological coping frameworks is effective in enhancing family well-being, especially in communities with socio-economic vulnerabilities.